1999
DOI: 10.1021/jp992358r
|View full text |Cite
|
Sign up to set email alerts
|

Time-Resolved Spectroscopic Studies of B12 Coenzymes:  The Photolysis of Methylcobalamin Is Wavelength Dependent

Abstract: Femtosecond to nanosecond transient absorption spectroscopy has been used to investigate the primary photochemistry of the B 12 coenzymes, methylcobalamin and 5′-deoxyadenosylcobalamin. Photolysis at excitation wavelengths in the near UV (400 nm) and visible (520-530 nm) are compared. Measurements were performed with femtosecond time resolution covering time delays of up to 9 ns. The photochemistry of methylcobalamin is found to depend strongly on excitation wavelength, while the photochemistry of adenosylcoba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
232
4

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(252 citation statements)
references
References 19 publications
(76 reference statements)
16
232
4
Order By: Relevance
“…As it is depicted in Figure 3: (a) the methylcobalamin-dependent methionine synthase generally includes as a primary turnover the cycling between Co(III) methylcobalamin and cob(I)alamin, which allows the heterolytic Co-C cleavage process, while in the adenosyl-cobalamin-dependent mutases the Co-C bond of adenosylcobalamin is cleaved homolytically, giving rise to a fi ve-coordinate cob(II)alamin and an adenosyl radical; (b) the association of the substrate and adenosyl-ligand during the Co-C cleavage process in adenosylcobalamin dependent mutases has been proved by various experimental data including X-ray diffraction results [35][36][37], while such effect is totally absent in studies regarding methylcobalamindependent mutases. The Co-C cleavage and electron transfer processes have been studied by different methods such as electrochemistry [38][39][40], thermo- [41] or photochemistry [42][43][44][45][46] of methylcobalamin Co(III) by a signifi cant number of researchers. As a result, many triggering factors of Co-C bond breaking have been considered and various mechanistic mechanisms of the Co-C cleavage process have been proposed.…”
Section: The Mechanisms Of Methylcobalamin and Adenosylcobalamin Actimentioning
confidence: 99%
“…As it is depicted in Figure 3: (a) the methylcobalamin-dependent methionine synthase generally includes as a primary turnover the cycling between Co(III) methylcobalamin and cob(I)alamin, which allows the heterolytic Co-C cleavage process, while in the adenosyl-cobalamin-dependent mutases the Co-C bond of adenosylcobalamin is cleaved homolytically, giving rise to a fi ve-coordinate cob(II)alamin and an adenosyl radical; (b) the association of the substrate and adenosyl-ligand during the Co-C cleavage process in adenosylcobalamin dependent mutases has been proved by various experimental data including X-ray diffraction results [35][36][37], while such effect is totally absent in studies regarding methylcobalamindependent mutases. The Co-C cleavage and electron transfer processes have been studied by different methods such as electrochemistry [38][39][40], thermo- [41] or photochemistry [42][43][44][45][46] of methylcobalamin Co(III) by a signifi cant number of researchers. As a result, many triggering factors of Co-C bond breaking have been considered and various mechanistic mechanisms of the Co-C cleavage process have been proposed.…”
Section: The Mechanisms Of Methylcobalamin and Adenosylcobalamin Actimentioning
confidence: 99%
“…56,58,60,65 To The dynamics of the photoinduced homolysis of B 12 cofactors were investigated on a time scale ranging from femtoseconds to nanoseconds, allowing for the detailed mechanism of Co-C bond photolysis to be obtained. In the case of CNCbl, it was found that the metastable S 1 state has a ligand-to-metal charge transfer (LMCT)…”
Section: Discussionmentioning
confidence: 99%
“…However, the excitation at 520 nm was followed only by formation of a long-lived S 1 state. 56,58,65 In contrast, the photolysis of AdoCbl was found to be wavelength independent resulting in a creation of a geminate radical pair within 100-130 ps at room temperature. 57,59,62 The same studies for ethyland n-propylcobalamin indicated the formation of radical pair when samples were excited at both 400 and 520 nm but the rapid dissociation contribution was mainly observed following the higher energy excitation.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations